External validation of leukocytosis and neutrophilia as a prognostic marker in anal carcinoma treated with definitive chemoradiation. Issue 1 (July 2017) - Schernberg, Antoine; Huguet, Florence; Moureau-Zabotto, Laurence; Chargari, Cyrus; Rivin Del Campo, Eleonor; Schlienger, Michel; Escande, Alexandre; Touboul, Emmanuel; Deutsch, Eric
Abstract: Purpose: To validate the prognostic value of leukocyte disorders in anal squamous cell carcinoma (SCC) patients receiving definitive concurrent chemoradiation. Materials and methods: Bi-institutional clinical records from consecutive patients treated between 2001 and 2015 with definitive chemoradiation for anal SCC were retrospectively reviewed. Prognostic value of pretreatment leukocyte disorders was examined, with focus on patterns of relapse and survival. Leukocytosis and neutrophilia were defined as leukocyte or neutrophil count exceeding 10 G/L and 7 G/L, respectively. Results: We identified 133 patients, treated in two institutions. Eight% and 7% displayed baseline leukocytosis and neutrophilia, respectively. Estimated 3-year overall survival (OS) and progression-free survival (PFS) were 88% and 77%, respectively. In univariate analysis, both leukocytosis and neutrophilia were associated with worse OS, PFS ( p  < 0.01), locoregional control (LRC) and Distant Metastasis Control (DMC) ( p  < 0.05), also after stratification by each institution. In multivariate analysis, leukocytosis and neutrophilia remained as independent risk factors associated with poorer OS, PFS, LRC and DMC ( p  < 0.05). Conclusion: This study validates leukocytosis and neutrophilia as independent prognostic factors in anal SCC patients treated with definitive chemoradiation. Although prospective confirmation is warranted, it is suggested that the leukocyte and neutrophil count parameters are clinically relevant biomarkers to be considered for further clinical investigations.